Interkit Reproducibility of the Indirect Immunofluorescence Assay on HEp-2 Cells Depends on the Immunofluorescence Reactivity Intensity and Pattern - Silva, Mônica Jesus; Dellavance, Alessandra; Baldo, Danielle Cristiane; Rodrigues, Silvia Helena; Grecco, Marcelle; Prado, Monica Simon; Agustinelli, Renan; Andrade, Luís Eduardo Coelho (Frontiers in Immunology, 2022)
Introduction The indirect immunofluorescence assay on HEp-2 cells (HEp-2/IFA) is used worldwide for screening for autoantibodies to cellular antigens. Cell culture and fixation methods influence the cell distribution of autoantigens and the preservation of epitopes. Therefore, discrepancy of results obtained using different HEp-2/IFA kits (interkit nonreproducibility) is a common phenomenon in the clinical laboratory routine. Objective This study evaluated the interkit nonreproducibility of HEp-2/IFA results using samples from patients with systemic autoimmune disease (SAD), nonautoimmune diseases (NAD), and healthy blood donors (HBD). Methods Serum from 275 SAD patients, 293 NAD patients, and 300 HBD were processed at 1:80 dilution using four HEp-2 kits according to the manufacturers’ instructions. Interkit reproducibility was determined for positive/negative results and patterns. The agreement of positive/negative results among kits for each sample was determined as the reactivity agreement score (RAS). The pattern reproducibility score (PRS) in each sample was calculated as a function of the number of kits showing equivalent patterns. Qualitative variables and ordinal variables were analyzed by the Chi-square and Mann-Whitney U tests, respectively. Results A total of 402 samples were nonreactive in all kits and were considered devoid of autoantibodies. Further analysis included the 466 reactive samples (238 SAD, 119 NAD, 109 HBD). Reactivity to the nucleus had the highest interkit reproducibility (RAS = 83.6), followed by the metaphase plate (RAS = 78.9), cytoplasm (RAS = 77.4), and nucleolus (RAS = 72.4). Interkit reproducibility was higher in SAD (RAS = 78.0) than in NAD (RAS = 70.6) and HBD (RAS = 71.3) groups. Samples with strong reactivity (++++/4 and +++/4) had higher interkit reproducibility than those with weak reactivity (+/4). In the SAD group, RAS for nuclear reactivity was 87.5% for strongly reactive samples as opposed to 4.4% for weakly reactive samples, and the same was observed for NAD and HBD samples. The most robust patterns were the centromere AC-3 (PRS = 78.4), multiple nuclear dots AC-6 (PRS = 73.6), nuclear coarse speckled AC-5 (PRS = 71.3), nuclear homogeneous AC-1 (PRS = 67.9), and the reticular cytoplasmic AC-21 (PRS = 68.6). Conclusion Interkit nonreproducibility in HEp-2/IFA is prevalent and occurs with the highest frequency with weakly reactive samples. International initiatives with the engagement of in vitro diagnostic industry are encouraged to promote the harmonization of the properties and performance of HEp-2/IFA commercial kits.